The H-2A Program and Immigration Reform in the United States - Berdikul Qushim; Zhengfei Guan; Fritz Roka (EDIS)
The Immigration and Nationality Act (INA) of 1952 authorized a nonimmigrant visa category, known as H-2, for foreign agricultural and nonagricultural workers to come to the United States and perform temporary services. To protect against disruptions in the farm labor supply, many growers are turning to the H-2A program to import foreign guest workers. This 5-page fact sheet written by Berdikul Qushim, Zhengfei Guan, and Fritz M. Roka and published by the UF/IFAS Food and Resource Economics Department explains the H-2A program and briefly discusses immigration reform. http://edis.ifas.ufl.edu/fe1029